La autoridad : eje de la acción-reflexión del practicante docente (2005)
ABSTRACT: It's presented the second port of the systematization result: Practice knowledge of Pedagogic Project on Malta and Pilsen elemental school s 1996-1997 analyzing the way that guided pedagogic action and its cornponents- teacher-pupil relation, method, arranging, of the class, motivator strategies, and evaluatiorytaking as transversal guide of reflection the management that teaching practice does with the authority in leading the class, taking into account the internal and external influences that motivated the meaningful changes in pedagogical action . Systematization was did it in order to understand and to cornrnunicate this experiences to the students who start their practice and live this process on the authority rnanagement in theclassroom.